Superordinate identities and self-transcendent emotions: Longitudinal study in Spain and Chile - Wlodarczyk, Anna; Méndez, Lander; Cusi, Olaia; Telletxea, Saioa; Mendia, Jara; Briceño, Mauricio; Delgado, Daniela; Balbontín, Francisca; Lecaros, Alexandra; Páez, Darío (Frontiers in Psychology, 2022)
Recent studies suggest that identification with all humanity, apart from being related to universalistic values, could also be related to self-transcendent emotions. In this scenario, the general objective of this cross-cultural longitudinal study is to examine the relationship between Identification with all Humanity (IWAH) subscales, that is, proximate identification categories (i.e., community and country) and superordinate ones (all humanity), and their association with positive self-oriented and self-transcendent emotions during a traumatic global phenomenon such as COVID-19 pandemics. Additionally, we also explore differences regarding the patterns of those associations in different cultural contexts (Chile and Spain) and whether they vary among two different time points (T1 - T2). The total sample was composed by 403 participants, of whom 224 were residents in Chile (M = 39.25, SD = 12.56; range 18 to 71 years; 49.6% women) and 179 were residents in Spain (M = 36.35, SD = 12.12; range 18 to 68 years; 59.8% women). Data collection was carried out in September (T1) and November (T2) 2020, through online surveys administered via Survey Monkey® platform. Overall results show a greater identification with proximate categories rather than superordinate ones, higher levels of self-transcendent emotions compared to self-oriented emotions, and a stronger association between self-transcendent emotions and all levels of identification. Analisis regarding comparisons between countries indicate higher levels of identification with community and all humanity in Spain and with country in Chile. Further, participants in Chile reported experimenting significantly more self-oriented and self-transcendent emotions, than in Spain. Moreover, we found greater strength of associations between the IWAH subscales and emotions in Chile. Finally, humanity subscale, and specifically its sub-dimension of concern, decreased significantly (T1-T2) in both countries. This could be considered as a symptom of growing fatigue with the pandemic situation, and also reflect a shift from broader to more local concerns. The results are discussed in the context of new developments in studies on identification with all humanity.